Determination of propiverine hydrochloride in human plasma by high performance liquid chromatographytandem mass spectrometry: application to the pharmacokinetic study of a sustained release formulation - Meihua, Huang; Yuan, Tian; Zunjian, Zhang; Hongwen, Zhang; Hui, Lin (Arzneimittelforschung, 2011)
A rapid, sensitive and reliable high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method was developed and validated for the determination of propiverine hydrochloride (CAS 54556-98-8) in human plasma using cetirizine di-hydrochloride as internal standard (IS, CAS 8388-51-0). Following liquid-liquid extraction with ethyl acetate, the separation was performed on a reverse phase C18 column with a mobile phase consisted of metha-nol-ammonium acetate (pH 4.0; 10 mM) (70:30, v/v). The detection was performed by a triple-quadrupole mass spectrometer in the positive ion and multiple reaction monitoring (MRM) mode, m/z 368.3 → 116.1 for propiverine and m/z 389.2 → 201.0 for the IS. The calibration curve fitted well over the concentration range of 0.2–200 ng/mL (all the concentration data in this study are related to salt (propiverine hydrochloride)). The limit of detection (LOD) and lower limit of quantification (LLOQ) in human plasma were 0.05 and 0.2 ng/mL, respectively. The method was proved to be rapid, sensitive, specific, accurate and reproducible and has been successfully applied to a pharmacokinetic study of propiverine hydrochloride sustained release capsules (the 30 mg dose in this
Keywords: Anticholinergic agent; HPLC-MS/MS; Human plasma; Pharmacokinetics; Propiverine hydrochloride; Sustained release